Telomere Length Dynamics and Chromosomal Instability in Cells Derived from Telomerase Null Mice - M. Prakash Hande; Enrique Samper; Peter M. Lansdorp; Marı́a A. Blasco (1999)
To study the effect of continued telomere shortening on chromosome stability, we have analyzed the telomere length of two individual chromosomes (chromosomes 2 and 11) in fibroblasts derived from wild-type mice and from mice lacking the mouse telomerase RNA (mTER) gene using quantitative fluorescence in situ hybridization. Telomere length at both chromosomes decreased with increasing generations of mTER−/− mice. At the 6th mouse generation, this telomere shortening resulted in significantly shorter chromosome 2 telomeres than the average telomere length of all chromosomes. Interestingly, the most frequent fusions found in mTER−/− cells were homologous fusions involving chromosome 2. Immortal cultures derived from the primary mTER−/− cells showed a dramatic accumulation of fusions and translocations, revealing that continued growth in the absence of telomerase is a potent inducer of chromosomal instability. Chromosomes 2 and 11 were frequently involved in these abnormalities suggesting that, in the absence of telomerase, chromosomal instability is determined in part by chromosome-specific telomere length. At various points during the growth of the immortal mTER−/− cells, telomere length was stabilized in a chromosome-specific man-ner. This telomere-maintenance in the absence of telomerase could provide the basis for the ability of mTER−/− cells to grow indefinitely and form tumors.